Integrating MOOCs in physics preliminary undergraduate education: beyond large size lectures. Issue 4 (2nd October 2018) - Raffaghelli, Juliana; Ghislandi, Patrizia; Sancassani, Susanna; Canal, Luisa; Micciolo, Rocco; Balossi, Barbara; Bozzi, Matteo; Di Sieno, Laura; Genco, Immacolata; Gondoni, Paolo; Pini, Andrea; Zani, Maurizio
ABSTRACT: In this paper, the authors discuss the effectiveness of MOOCs as part of a pedagogical strategy aimed at supporting Physics' preliminary undergraduate students in large-size lectures. Our study is based on an experimental activity based on a blended course, which integrated a parallel MOOC delivered through the POK (PoliMi Open Knowledge, http://www.pok.polimi.it ), the Politecnico di Milano's MOOC portal. The blended model also delivered face-to-face activities that included intensive technology enhanced learning, like feedback based on clickers. Specifically, we introduce the several elements of the approach (the tutors' pedagogy, the adoption of clickers, the diversity amongst learning groups) and its process of implementation. The findings in this study highlight that the integrated model is effective in terms' of students' learning both for small and large size lectures. More importantly, it was found that the students in large size lectures demonstrated similar or even better performance than students in a small size group. Moreover, the students in all sizes lectures showed higher satisfaction with the MOOCs' against other factors adopted within the learning design.